Role of Antonymy in Conceptualization of Sound Characteristics in Russian Language - T. M. Voronina (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
On the basis of the ideographic dictionary data, semantic relations within the framework of synonymic-antonymic complexes in the denotative-ideographic group “Sound Characteristics” in the modern Russian language are considered. The symmetry / asymmetry of these relations is shown. Specifics of conceptualization of the characteristics of the sound in the aspect of relations of opposites is revealed. The study was conducted in the framework of the project of Big Comprehensive Ideographic Dictionary of Synonymic and Antonymic Complexes under the direction of L. G. Babenko. The relevance of the study is due to the fact that the antonymy in the field of sound is considered comprehensively, in interaction with synonymic connections, as well as in the aspect of lexicographic representation. The material of the study was seven synonymic and antonymic complexes: blagozvuchnyy - neblagozvuchnyy, vnyatnyy - nevnyatnyy, vysokiy - nizkiy, gromkiy - tikhiy, zvonkiy - glukhoy, pronzitelnyy - myagkiy, protyazhnyy - otryvistyy . The differences in the “fullness” of synonymic-antonymic oppositions and the ratio of synonyms and antonyms in them are noted. It is shown that an important parameter for the oppositions under consideration is the objective / subjective nature of the feature. The types of antonymy oppositions implemented in the field of sound are considered: contradictory oppositions name mutually exclusive characteristics of sound; contrary oppositions have gradable parameter in semantics, which causes the opposition; contrary nature of these oppositions is emphasized by the presence of derivatives of the verbal oppositions of vector type.